THE IMPACT OF FOOD VISUAL AESTHETICS ON CONSUMER PERCEPTION OF A HEALTHY AND TASTY MEAL IN THE HOSPITALITY AND TOURISM INDUSTRY - Janjić, Ljubica; Vujović, Sonja; Zdravković, Ivica; Ilić, Dragana (Economics of Agriculture, 2023)
The visual appearance of food is an important attribute when people choose food. This paper aims to examine the impact of visual aesthetics on the consumer’s perception of a healthy and tasty meal. The paper consists of two empirical researches, which includes survey and experimental research. The survey results indicate the connection between the visual appearance of meals and the consumer’s perception of health and tasty meals. The experimental research compare consumer expectations about the meal taste based on its visual appearance, and actual consumer experience after tasting that meal. The results show that there are differences in consumer expectations, based on visual aesthetics and they should assist the hospitality and tourism business from acknowledging how the visual aesthetics of food can influence consumers’ food choice decisions. This can be an effective technique for hospitality and tourism companies in attracting consumers and increasing their loyalty.